2016
DOI: 10.1021/acs.langmuir.5b04429
|View full text |Cite
|
Sign up to set email alerts
|

Ramping of pH Across the Water-Pool of a Reverse Micelle

Abstract: In this work, we have addressed the problem of "acidity" of the water-pool of a reverse micelle (RM) through the well-known inversion of sucrose reaction as a tool of investigation. This reaction has been performed inside positively and negatively charged RM and the rates are compared with that in bulk water. We propose that the buffer-like action in a water-pool is much stronger than expected earlier. The rate of sucrose hydrolysis slowed down in the negatively charged AOT reverse micelle while it sped up for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
(65 reference statements)
2
14
0
Order By: Relevance
“…A concept proposed by some researchers [96], but not generally accepted [97], is the buffer-like action of water from RM due to the effect of titratable head groups of surfactant, the component with the higher concentration in the RM aggregates. This behavior it was reported especially for AOT surfactant which maintains the inside pH values to 5.0-5.5 for any value of the bulk buffer used, while the surfactant mixture CTAB/hexanol has a very low buffering capacity in the experimental range of pH from 4 to 10 [94].…”
Section: Ph Across the Water-poolsupporting
confidence: 70%
See 1 more Smart Citation
“…A concept proposed by some researchers [96], but not generally accepted [97], is the buffer-like action of water from RM due to the effect of titratable head groups of surfactant, the component with the higher concentration in the RM aggregates. This behavior it was reported especially for AOT surfactant which maintains the inside pH values to 5.0-5.5 for any value of the bulk buffer used, while the surfactant mixture CTAB/hexanol has a very low buffering capacity in the experimental range of pH from 4 to 10 [94].…”
Section: Ph Across the Water-poolsupporting
confidence: 70%
“…Besides the methods using optical pH sensor or molecular probe, Mukherjee &coworkers [94] proposed the acid-catalyzed hydrolysis of sucrose [95], respectively the inversion of sucrose, reaction monitorized by the rotation of polarized light. Their study was based on two working hypothesis: (i) the neutral molecule of sucrose will be located inside the water pool; (ii) the availability of protons inside the water-pool will affect the rate of sucrose hydrolysis in micellar medium compared with the reaction rate in bulk-water.…”
Section: Ph Across the Water-poolmentioning
confidence: 99%
“…The pKa values for (protonated) o ‐, m ‐ and p ‐fluoroaniline isomers are, 3.20, 3.59 and 4.65, respectively , suggesting that protonation might be to blame; addition of a small amount of triethylamine (Fig. b) gave sharp signals for all three isomers, confirming that the acidity of the water pool in the AOT solution was causing transient protonation of the most basic of the three isomers ( p ‐fluoroaniline).…”
Section: Resultsmentioning
confidence: 89%
“…At present, it is not possible to explain this effect. Mukherjee et al [46] had reported that a proton gradient exists inside the water-pool of charged reverse micelles. Possibly, in our case the reverse micelle is non-ionic in nature with nonpolarizable groups, thus no proton gradient is present which may affect the enzyme activity.…”
Section: Encapsulation Of Go X In Microemulsionmentioning
confidence: 99%